Ionic liquids in novel processing ways to obtain chitosan-silk fibroin hydrogels for skin tissue engineering - Silva, Simone Santos (2011)
FCT (Project PTDC/QUI/68804/2006) and FEDER through POCTEP 0330_ IBEROMARE_1_P.